O Jardim da Infância Público anexo à Escola Normal da Praça: um estudo sobre o gênero (1896-1926) - Aird, Maitê Custódio Rios (2015)
This research aims to analyze how demarcated gender differences, more precisely what type of education was given to boys and girls, mediated by the requirements of the teaching method in froebeliano First Kindergarten Public annex to the Normal School Square which represented the starting point in ranking of public services for children. The intention is to understand the different mechanisms that were the way boys and girls were educated, unraveling the plot that organized the masculinity and femininity that this school spread.Thinking of an administration of sex differences within the school curriculum is necessary to observe the curriculum of early childhood education in the interrelation between prescriptions, family and school. There is the analysis of the pedagogical proposal of the Kindergarten and gender relations assigned to an activity called "Toys", considered scenic representations for everyday simulations and knowledge of things. The investigation found that the records of the scenarios previously demarcated the boy and girl role. The time frame covers the opening period of the kindergarten in 1896 until 1926, when it stands the use of the ideas of Friedrich Froebel, founder of the Kindergarten, primary guide of the practices in question. The hypothesis is that in this first collective insertion space of boys and girls, gender meanings are translated in the material sphere, in relations, in pedagogical resources used by gardeners and relationships with children and their families, sometimes so veiled, naturalized. Thus, it was studied the relevant literature and documents found in the history Caetano de Campos School Collection, emphasizing the Education Magazine (1912), Journal of kindergarten (1896 and 1897), the Toys record book (1903), photo albums, registration book (1896-1908) and inventories (1896-1947) and then newspapers, among others